2010
DOI: 10.1002/jnr.22530
|View full text |Cite
|
Sign up to set email alerts
|

Whisker experience modulates long‐term depression in neocortical γ‐aminobutyric acidergic interneurons in barrel cortex

Abstract: Long-term plasticity is believed to be an important mechanism that allows neural circuits to be modulated in an use-dependent manner. However, evidence regarding the role of sensory experience in modulating long-term plasticity of glutamatergic synapses in neocortical GABAergic interneurons is unavailable. Here, we focused on regular-spiking nonpyramidal (RSNP) interneurons and examined spike-pairing-induced plasticity of glutamatergic synapses and its modulation by sensory experiences ex vivo. In our previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…In FS interneurons of the somatosensory cortex, in contrast, one study reported mGluR-dependent LTD whether the presynaptic spike preceded or followed the postsynaptic spike (Lu et al, 2007). A similar pattern was observed at intracortical glutamatergic synapses on regular-spiking interneurons in barrel cortex (Sun and Zhang, 2011). mGluR5 receptors also play a central role in NMDA-independent LTP of excitatory postsynaptic potentials in FS interneurons of the visual cortex (Sarihi et al, 2008).…”
Section: Ltp and Ltd At Glutamatergic Synapses On Interneuronsmentioning
confidence: 95%
See 1 more Smart Citation
“…In FS interneurons of the somatosensory cortex, in contrast, one study reported mGluR-dependent LTD whether the presynaptic spike preceded or followed the postsynaptic spike (Lu et al, 2007). A similar pattern was observed at intracortical glutamatergic synapses on regular-spiking interneurons in barrel cortex (Sun and Zhang, 2011). mGluR5 receptors also play a central role in NMDA-independent LTP of excitatory postsynaptic potentials in FS interneurons of the visual cortex (Sarihi et al, 2008).…”
Section: Ltp and Ltd At Glutamatergic Synapses On Interneuronsmentioning
confidence: 95%
“…Although equivalent data are not available in the somatosensory cortex, whisker trimming has been shown to facilitate LTD of glutamatergic synapses elicited by an STDP protocol in regular-spiking interneurons (Sun and Zhang, 2011). Recent in vivo imaging has also revealed extensive structural plasticity of GABAergic synapses affected by whisker trimming van Versendaal et al, 2012).…”
Section: Adaptive Roles Of Plasticity Of Inhibitionmentioning
confidence: 99%
“…53,54 In canonical cortical circuitry, L2/3 receives its prominent excitatory drive from L4 and subsequently sends a major output to L5B. 40 In a healthy barrel cortex, L2/3 PCs display a lower synaptic E/I ratio compared to L5B PCs within the same columns, 29,51,55 consistent with their respective functions, e.g., the sparse coding strategy used by supragranular neurons for feature integration 56,57 and active feedback to subcortical regions. 34,58 L2/3 PCs also send their outputs to other ipsi-and contra-lateral cortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that synaptic excitation and inhibition in cortical neurons show a proportionality, or balance, through the use of recurrent local synaptic connections to maintain normal brain functions. 29,37,[47][48][49][50][51][52] L2/3 and L5B PCs play different roles in the horizontal propagation of recurrent-network activities, including epileptiform activities. 53,54 In canonical cortical circuitry, L2/3 receives its prominent excitatory drive from L4 and subsequently sends a major output to L5B.…”
Section: Discussionmentioning
confidence: 99%